Greenhouse monitoring and harvesting mobile robot with 6DOF manipulator utilizing ROS, inverse kinematics and deep learning models - Islam, Md. Hashibul; Wadud, Md. Firoz; Rahman, Md. Raihan; Alam, A S M Hasibul (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.